Students’ Perspective on the Translingual Practice in Their English Writing - Muhammad Ilhamsyah Fauzan Akbar; Hilda Izzati Madjid; Irvi Puspitasari (Raja Zulkarnain Education Foundation, 2025)
This study explores students’ perspective on Translingual Practice in students' English writing. Translingualism is known as a phenomenon of maximizing potential using more than language, and it values multiple languages as a resource for making meaning in communication. In this study using qualitative descriptive as an approach, data were collected by semi-structured interviews with ten students from SMA Al-Falah Ketintang Surabaya. The findings reveal students’ perspectives in using multiple languages in English writing. Some view language mixing as a creative and helpful way to convey ideas, while others consider it inappropriate in formal writing. Most students also show limited awareness of the concept, though they unconsciously engage in similar practices.